Long noncoding RNA PWRN1 is lowly expressed in osteosarcoma and modulates cancer proliferation and migration by targeting hsa‐miR‐214‐5p. Issue 11 (1st September 2020) - Shi, Jiyuan; Fu, Qiang; Yang, Pei; Yi, Zhi; Liu, Shizhang; Wang, Kunzheng
Abstract: Background: We examined the expression pattern, clinical relevance, and molecular mechanisms of lncRNA PWRN1 in human osteosarcoma. Methods: qPCR was used to measure PWRN1 expressions in cell lines and tumor samples osteosarcoma. The correlations between PWRN1 and cancer patients' clinicopathological properties and survival were examined. PWRN1 was ectopically overexpressed in MG‐63 and 143B cells to assess its function on cancer cell proliferation, cisplatin chemoresistance, and in vivo xenotransplant growth. The ceRNA candidate of PWRN1, miR‐214‐5p was examined in osteosarcoma cells. In addition, miR‐214‐5p and PWRN1 were double‐overexpressed in osteosarcoma cells to investigate the regulatory role of epigenetic axis PWRN1/miR‐214‐5p in osteosarcoma. Results: We found that PWRN1 was downregulated in both osteosarcoma cells and human tumors. PWRN1 downregulation was correlated with advanced stage, metastasis, and low survival rate in cancer patients. PWRN1 overexpression in osteosarcoma cells significantly inhibited their proliferation, cisplatin chemoresistance, and in vivo growth. In addition, we demonstrated that PWRN1 directly bound miR‐214‐5p and suppressed its expression in osteosarcoma cells. Furthermore, we showed that miR‐214‐5p overexpression reversed the anti‐cancer effects of PWRN1 on osteosarcoma cell proliferation and cisplatin chemoresistance. Conclusion: Our data provide new insights into the epigenetic axis of PWRN1/miR‐214‐5p in regulating osteosarcoma progression and chemoresistance. PWRN1 may also be a biomarker to predicting cancer patients' poor prognosis and novel pharmaceutical targets for personalized medicine.